Chloramphenicol acetyltransferase, a cytoplasmic protein is incompatible for export from Bacillus subtilis. - Chen, M W (1993)
Bacillus subtilis cells expressing a hybrid protein (Lvsss-Cat) consisting of the B. amyloliquefaciens levansucrase signal peptide fused to B. pumilus chloramphenicol acetyltransferase (Cat) are unable to export Cat protein into the growth medium. A series of tripartite protein fusions was constructed by inserting various lengths of the Cat sequences between the levansucrase signal peptide and staphylococcal protein A or Escherichia coli alkaline phosphatase. Biochemical characterization of the various Cat protein fusions revealed that multiple regions in the Cat protein were causing the export defect.